1996
DOI: 10.1046/j.1420-9101.1996.9050519.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and radiation of the house mouse: clues from nuclear genes

Abstract: Although quite a lot is known about the genetic structure of the polytypic species Mus musculus at the periphery of its range, the centre of origin and dispersion of the species remains unknown. To investigate the amount of genetic subdivision that occurs in the central parts of its range, we analysed the genetic variation in four new samples of mice coming from Iran, Pakistan, northern and southern India using 3.5 autosomal protein loci and restriction fragment length polymorphisms of three genes of the Vg ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 42 publications
8
90
0
4
Order By: Relevance
“…Evolutionary models suggest that the three major mouse subspecies diverged simultaneously from a common ancestor or, alternatively, that M. m. musculus and M. m. castaneus diverged from a common ancestor shortly after the divergence of M. m. domesticus [26][27][28] . This history should be reflected in the distribution of SNPs that are specific to each of the subspecies.…”
Section: Diagnostic Snpsmentioning
confidence: 99%
“…Evolutionary models suggest that the three major mouse subspecies diverged simultaneously from a common ancestor or, alternatively, that M. m. musculus and M. m. castaneus diverged from a common ancestor shortly after the divergence of M. m. domesticus [26][27][28] . This history should be reflected in the distribution of SNPs that are specific to each of the subspecies.…”
Section: Diagnostic Snpsmentioning
confidence: 99%
“…Under this scenario, the derived MUS and BAC types developed in situ, each in different areas of the Indian subcontinent. However, MUS types later dispersed out from this region, again moving both west and east, where they eventually established secondary contact with the DOM and CAS populations, respectively Din et al, 1996). An alternative view, derived from analyses of mitochondrial and some nuclear gene sequences, postulates a Middle Eastern origin of M. musculus, with subsequent dispersal of DOM, MUS, CAS and GEN types to Western Europe, northern Eurasia, India and the Arabian Peninsula, respectively (note that sequence data generally fail to identify a separate BAC cluster).…”
Section: Introductionmentioning
confidence: 99%
“…Based on allozyme data sets, several research teams have proposed that M. musculus emerged in central Asia or India, and dispersed in both west and east, giving rise to DOM and CAS in Europe and East Asia, respectively Din et al, 1996). Under this scenario, the derived MUS and BAC types developed in situ, each in different areas of the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be encountered in the countryside (rice fields, savannas, borders of marshes) but at very low densities. The house mouse (Mus musculus species complex) originated from the Indian subcontinent Din et al, 1996). It is assumed that it radiated approximately 0.5 million years ago in three directions, thus giving rise to the current subspecies (which some authors consider as proper species, see Sage et al, 1993) Prager et al (1998) suggested that a gentilulus lineage may exist on the Arabian peninsula (which would represent a subspecies according to the nomenclature adopted in the present article, but a species according to the original article), based on a divergent mitochondrial lineage recently described in Yemen.…”
Section: Introductionmentioning
confidence: 99%